Village Libraries as Knowledge Nodes in the Era of Globalization: A Systematic Literature Review in Indonesia - Idamayanti, Ariska (Inkunabula: Journal of Library Science and Islamic Information, 2026)
This study aims to analyze the role of village libraries as knowledge nodes in the context of globalization by examining their contributions, transformation dynamics, challenges, and strengthening strategies in Indonesia. The research employs a Systematic Literature Review (SLR) approach on 13 relevant journal articles published between 2020 and 2025. The articles were selected based on predetermined inclusion and exclusion criteria and analyzed using thematic analysis to identify patterns of transformation and institutional strengthening strategies of village libraries. The findings indicate that village libraries have transformed from passive collection-based institutions into multidimensional literacy centers, community empowerment hubs, and agents of social transformation. Their contributions include the development of reading literacy, information literacy, and digital literacy, as well as the enhancement of local community capacity, creativity, and skills. However, village libraries still face several structural challenges, including limited human resources, collections, facilities, funding, and gaps in digital infrastructure. The study highlights the strategic potential of village libraries as knowledge nodes that connect global information flows with the local needs of communities. The novelty of this research lies in the conceptual reconstruction of village libraries from a knowledge connectivity perspective that integrates literacy, information connectivity, and social empowerment within the framework of globalization. These findings contribute theoretically to the development of library and information science studies and provide practical implications for strengthening sustainable knowledge-based rural development. Abstrak Penelitian ini bertujuan menganalisis peran perpustakaan desa sebagai simpul pengetahuan dalam konteks globalisasi dengan mengkaji kontribusi, dinamika transformasi, tantangan, serta strategi penguatannya di Indonesia. Penelitian menggunakan pendekatan Systematic Literature Review (SLR) terhadap 13 artikel jurnal yang relevan dan dipublikasikan pada periode 2020–2025. Artikel dipilih berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan, kemudian dianalisis menggunakan analisis tematik untuk mengidentifikasi pola transformasi dan strategi penguatan kelembagaan perpustakaan desa. Hasil penelitian menunjukkan bahwa perpustakaan desa mengalami transformasi dari institusi berbasis koleksi pasif menjadi pusat literasi multidimensi, pemberdayaan masyarakat, dan transformasi sosial. Kontribusinya mencakup pengembangan literasi baca-tulis, literasi informasi, dan literasi digital, serta peningkatan kapasitas, kreativitas, dan keterampilan masyarakat lokal. Namun demikian, perpustakaan desa masih menghadapi berbagai tantangan struktural, seperti keterbatasan sumber daya manusia, koleksi, fasilitas, anggaran, serta kesenjangan infrastruktur digital. Penelitian ini menegaskan bahwa perpustakaan desa memiliki potensi strategis sebagai simpul pengetahuan yang menghubungkan arus informasi global dengan kebutuhan lokal masyarakat. Kebaruan penelitian terletak pada rekonstruksi konseptual perpustakaan desa dalam perspektif konektivitas pengetahuan yang mengintegrasikan dimensi literasi, konektivitas informasi, dan pemberdayaan sosial dalam kerangka globalisasi. Temuan ini memberikan kontribusi teoretis bagi pengembangan kajian ilmu perpustakaan dan informasi serta implikasi praktis bagi penguatan pembangunan desa berbasis pengetahuan yang berkelanjutan.